Longitudinal assessment of plasma biomarkers for early detection of cognitive changes in subjective cognitive decline - Hsieh, Cheng-Hao; Ko, Chien-An; Liang, Chih-Sung; Yeh, Po-Kuan; Tsai, Chia-Kuang; Tsai, Chia-Lin; Lin, Guan-Yu; Lin, Yu-Kai; Tsai, Ming-Chen; Yang, Fu-Chi (Frontiers in Aging Neuroscience, 2024)
Background: Individuals experiencing subjective cognitive decline (SCD) are at an increased risk of developing mild cognitive impairment and dementia. Early identification of SCD and neurodegenerative diseases using biomarkers may help clinical decision-making and improve prognosis. However, few cross-sectional and longitudinal studies have explored plasma biomarkers in individuals with SCD using immunomagnetic reduction. Objective: To identify plasma biomarkers for SCD. Methods: Fifty-two participants (38 with SCD, 14 healthy controls [HCs]) underwent baseline assessments, including measurements of plasma Aβ42, Aβ40, t-tau, p-tau, and α-synuclein using immunomagnetic reduction (IMR) assays, cognitive tests and the Mini-Mental State Examination (MMSE). Following initial cross-sectional analysis, 39 individuals (29 with SCD, 10 HCs) entered a longitudinal phase for reassessment of these biomarkers and the MMSE. Biomarker outcomes across different individual categories were primarily assessed using the area under the receiver operating characteristic (ROC) curve. The SCD subgroup with an MMSE decline over one point was compared to those without such a decline. Results: Higher baseline plasma Aβ1-42 levels significantly discriminated participants with SCD from HCs, with an acceptable area under the ROC curve (AUC) of 67.5% (95% confidence interval [CI], 52.7%–80.0%). However, follow-up and changes in MMSE and IMR data did not significantly differ between the SCD and HC groups (P >0.05). Furthermore, lower baseline plasma Aβ1-42 levels were able to discriminate SCD subgroups with and without cognitive decline with a satisfied performance (AUC, 75.0%; 95% CI, 55.6%–89.1%). At last, the changes in t-tau and Aβ42 × t-tau could differentiate between the two SCD subgroups (P <0.05). Conclusion: Baseline plasma Aβ42 may help identify people with SCD and predict SCD progression. The role of plasma Aβ42 levels as well as their upward trends from baseline in cases of SCD that progress to mild cognitive impairment and Alzheimer’s disease require further investigation.